Seasonal Variation of the Water Quality of the Senegal River (Mauritania) (International Journal of Chemical and Process Engineering Research, 2014)
The aim ofthis studyis to monitor and to assessthe physicochemicalwater qualityof the river Senegal during the rainy and dry season. The conventional physico-chemical parameters (pH, EC and DO), dissolved and suspended particles (turbidity and TSS), OM and nitrateswere considered in this study. The samples are collected at the Beni Nadji site between February and November 2012. The values of the measured parameters were compared with WHO standards for drinking water quality. The findings show that all the physicochemical parameters measured were within the tolerable values except the turbidity and TSS that exceeded with respectively the maximum values of 980 NTU and 674 mg/L for the rainy season only. The analysis of the correlation matrix can be noted strong correlations between the turbidity and TSS (0.996), turbidity and OM (0.924), TSS and OM (0.931), nitrates and TSS (0.814), nitrates and turbidity (0.800) and nitrates and OM (0.744). These strong correlations allow us to say that these parameters are governed by the same mechanism or phenomenon that could possibly be leaching during the rainy season. Therefore, frequent monitoring of physicochemical parameters of Senegal River water resources is imperative.